Probing the nature of high-redshift weak emission line quasars: a young quasar with a starburst host galaxy - Andika, Irham Taufik; Jahnke, Knud; Onoue, Masafusa; Bañados Torres, Eduardo; Mazzucchelli, Chiara; Novak, Mladen; Eilers, Anna-Christina; Venemans, Bram P.; Schindler, Jan-Torge; Walter, Fabian; Neeleman, Marcel; Simcoe, Robert A.; et al. (The astrophysical journal, 2020)
We present the discovery of PSO J083.8371+11.8482, a weak emission line quasar with extreme star formation rate at z = 6.3401. This quasar was selected from Pan-STARRS1, UHS, and unWISE photometric data. Gemini/GNIRS spectroscopy follow-up indicates a Mg ii-based black hole mass of M ⊙ and an Eddington ratio of , in line with an actively accreting supermassive black hole (SMBH) at z ≳ 6. Hubble Space Telescope imaging sets strong constraint on lens boosting, showing no relevant effect on the apparent emission. The quasar is also observed as a pure point source with no additional emission component. The broad-line region (BLR) emission is intrinsically weak and not likely caused by an intervening absorber. We found rest-frame equivalent widths of EW , EW Å (3σ upper limit), and EW . A small proximity zone size ( pMpc) indicates a lifetime of only years from the last quasar phase ignition. ALMA shows extended [C ii] emission with a mild velocity gradient. The inferred far-infrared luminosity () is one of the highest among all known quasar hosts at z ≳ 6. Dust and [C ii] emissions put a constraint on the star formation rate of SFR = 900-, similar to that of a hyperluminous infrared galaxy. Considering the observed quasar lifetime and BLR formation timescale, the weak-line profile in the quasar spectrum is most likely caused by a BLR that is not yet fully formed rather than by continuum boosting by gravitational lensing or a soft continuum due to super-Eddington accretion.